2015
DOI: 10.1557/opl.2015.762
|View full text |Cite
|
Sign up to set email alerts
|

P-type Doping of Organic Charge Transport Materials with Tungsten Oxide

Abstract: The effects of WO3 doping in 4,4’-bis-9-carbozyl biphenyl (CBP) were studied through detailed electrical device characterization. A series of hole-only devices have been fabricated, where the doping level was varied from 10-40mol% and the doped CBP thickness was varied from 5-40 nm. It was found that, to achieve effective doping for improved hole injection and transport, the doping level should be greater than 20mol% and the doped layer should be at least 10 nm thick. It was also found that an energy barrier e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Cao et al reported p-type doped organic charge transport materials with tungsten oxide for OLEDs [25]. Nevertheless, the organic HTLs reveals some disadvantages such as low solubility in organic solvents and an unsuitable work-function along with high aggregation of materials while thin film formation [25,26]. Therefore, the solution processable HTL materials performance should be enhanced to attain a highlyefficient OLED.…”
Section: Introductionmentioning
confidence: 99%
“…Cao et al reported p-type doped organic charge transport materials with tungsten oxide for OLEDs [25]. Nevertheless, the organic HTLs reveals some disadvantages such as low solubility in organic solvents and an unsuitable work-function along with high aggregation of materials while thin film formation [25,26]. Therefore, the solution processable HTL materials performance should be enhanced to attain a highlyefficient OLED.…”
Section: Introductionmentioning
confidence: 99%